2018
DOI: 10.1083/jcb.201710087
|View full text |Cite
|
Sign up to set email alerts
|

LITE microscopy: Tilted light-sheet excitation of model organisms offers high resolution and low photobleaching

Abstract: Fadero et al. present lateral interference tilted excitation (LITE) microscopy–a tilted light-sheet method to illuminate high-numerical-aperture objectives for fluorescence microscopy. LITE can be implemented unobtrusively on most microscope systems and combines low photodamage with high resolution and efficient detection in imaging fluorescent organisms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…Studies that used H. exemplaris strain Z151 prior to the 2018 species disambiguation from H. dujardini (Gasiorek et al 2018) generally referred to the species as H. dujardini, or as Hypsibius cf. dujardini, and in many of these studies the strain was indicated as Z151 and/or sourced from Sciento Bavan et al 2009;Mali et al 2010;Cesari et al 2012;Beltrán-Pardo et al 2013;Horikawa et al 2013;Tenlen et al 2013;Smith and Jockusch 2014;Boothby et al 2015Boothby et al , 2017Gross and Mayer 2015;Kondo et al 2015;Arakawa et al 2016;Bemm et al 2016;Fernandez et al 2016;Hering et al 2016;Hyra et al 2016a,b;Kosztyła et al 2016;Koutsovoulos et al 2016;Levin et al 2016;Smith et al 2016Stec et al 2016;Erdmann et al 2017;Gross et al 2017Gross et al , 2018Vasanthan et al 2017;Yoshida et al 2017Yoshida et al , 2018Fadero et al 2018;Nelson 2018;Rost-Roszkowska et al 2018). One study using Thulinia stephaniae (Hejnol and Schnabel 2005) indicates some contrasting developmental features in a second tardigrade species.…”
Section: Related Speciesmentioning
confidence: 99%
“…Studies that used H. exemplaris strain Z151 prior to the 2018 species disambiguation from H. dujardini (Gasiorek et al 2018) generally referred to the species as H. dujardini, or as Hypsibius cf. dujardini, and in many of these studies the strain was indicated as Z151 and/or sourced from Sciento Bavan et al 2009;Mali et al 2010;Cesari et al 2012;Beltrán-Pardo et al 2013;Horikawa et al 2013;Tenlen et al 2013;Smith and Jockusch 2014;Boothby et al 2015Boothby et al , 2017Gross and Mayer 2015;Kondo et al 2015;Arakawa et al 2016;Bemm et al 2016;Fernandez et al 2016;Hering et al 2016;Hyra et al 2016a,b;Kosztyła et al 2016;Koutsovoulos et al 2016;Levin et al 2016;Smith et al 2016Stec et al 2016;Erdmann et al 2017;Gross et al 2017Gross et al , 2018Vasanthan et al 2017;Yoshida et al 2017Yoshida et al , 2018Fadero et al 2018;Nelson 2018;Rost-Roszkowska et al 2018). One study using Thulinia stephaniae (Hejnol and Schnabel 2005) indicates some contrasting developmental features in a second tardigrade species.…”
Section: Related Speciesmentioning
confidence: 99%
“…SPIM has been used to visualize large living biological systems such as zebrafish, 11,12 Drosophila melanogaster embryos, 13 Caenorhabditis elegans, 14 tumor cell spheroids, 15,16 and Arabidopsis thaliana. 17 Different LSFM configurations have been proposed to perform multicolor 3-D imaging. [18][19][20][21] For instance, Krieger et al performed dual color fluorescence imaging using a single camera and two separate color channels, while Jahr et al used a diffractive unit to spectrally split the images onto a camera in order to obtain hyperspectral images.…”
Section: Introductionmentioning
confidence: 99%
“…The most notable of these techniques is lattice light sheet, where a two-dimensional optical lattice is used to create thin, structured illumination sheets that are dithered during a single exposure [14]. Traditionally LSFM requires two objective lenses, one for illumination and one for detection, placed at a 90-degree angle relative to each other such that the light sheet from the illumination source coincides with the imaging plane of the detection objective [14][15][16][17][18][19][20][21]. Such systems can be less user-friendly than conventional microscopes.…”
Section: Introductionmentioning
confidence: 99%